A Novel Semiautomated Pipeline to Measure Brain Atrophy and Lesion Burden in Multiple Sclerosis: A Long-Term Comparative Study - Uher, Tomas; Krasensky, Jan; Vaneckova, Manuela; Sobisek, Lukas; Seidl, Zdenek; Havrdova, Eva; Bergsland, Niels; Dwyer, Michael G; Horakova, Dana; Zivadinov, Robert (Journal of neuroimaging, 2017)
BACKGROUND AND PURPOSE: Lesion burden and brain volume changes are frequent end points in research but nowadays are becoming important in the clinical practice of multiple sclerosis (MS). The objective of this study was to investigate the correlation between magnetic resonance imaging (MRI) measures obtained by in-house developed ScanView software and commonly used volumetric techniques for assessment of T2 lesion and whole brain volumes and their changes. METHODS: Together 3,340 MRI scans from 209 patients after first demyelinating event suggestive of MS, 181 relapsing-remitting MS patients and 43 controls were analyzed. The average number of MRI scans and follow-up duration was 8.2 and 6.5 years, respectively. All MRI scans were performed in a single center but independently analyzed in two neuroimaging centers. Volumetric analysis by ScanView software was applied in Prague. Commonly used techniques, such as SIENA, SIENAX, and Jim software, were applied in Buffalo. Correlations between MRI measures were evaluated using correlation coefficients. Intraindividual variability of longitudinal MRI data was estimated by mean squared error. RESULTS: The associations of the cross-sectional and longitudinal MRI measures between commonly used techniques and ScanView were significant (r/rho = .83-.95). The associations of cross-sectional MRI measures were stronger (r/rho = .90-.95) compared with longitudinal ones (r = .83). Standardized intraindividual variability of whole brain % volume change was greater in ScanView compared with SIENA (mean squared error .32 vs. .21; P < .001). CONCLUSIONS: We found relatively strong correlations of cross-sectional and longitudinal data obtained by both techniques. However, SIENA showed lower intraindividual variability than the ScanView method in measuring whole brain volume loss over time.
Keywords: multiple sclerosis; dospělí; volumetry; Magnetic Resonance Imaging; Female; Adult; ženské pohlaví; průřezové studie; longitudinální studie; imunologické faktory; neurozobrazování; lidé; Multiple Sclerosis; magnetická rezonanční tomografie; roztroušená skleróza; mozek; atrofie; Cross-Sectional Studies; Immunologic Factors; Male; brain atrophy; Atrophy; Brain; lidé středního věku; MRI; mužské pohlaví; T2 lesion volume; Middle Aged; Neuroimaging; Longitudinal Studies; Humans